Burkholderia terrae BS001 migrates proficiently with diverse fungal hosts through soil and provides protection from antifungal agents - Nazir, Rashid; Tazetdinova, Diana I.; van Elsas, Jan Dirk (Frontiers in Microbiology, 2014)
Soil bacteria can benefit from co-occurring soil fungi in respect of the acquisition of carbonaceous nutrients released by fungal hyphae and the access to novel territories in soil. Here, we investigated the capacity of the mycosphere-isolated bacterium Burkholderia terrae BS001 to comigrate through soil along with hyphae of the soil fungi Trichoderma asperellum, Rhizoctonia solani, Fusarium oxysporum, Fusarium oxysporum pv lini, Coniochaeta ligniaria, Phaenerochaete velutina and Phallus impudicus. We used Lyophyllum sp. strain Karsten as the reference migration-inciting fungus. Bacterial migration through presterilized soil on the extending fungal hyphae was detected with six of the seven test fungi, with only Phallus impudicus not showing any bacterial transport. Much like with L. sp. strain Karsten, intermediate (106-108 CFU g-1 dry soil) to high (>108 CFU g-1 dry soil) strain BS001 cell population sizes were found at the hyphal migration fronts of four fungi, i.e. Trichoderma asperellum, Rhizoctonia solani, Fusarium oxysporum and Fusarium oxysporum pv lini, whereas for two fungi, Coniochaeta ligniaria and Phaenerochaete velutina, the migration responses were retarded and population sizes were lower (103-106 CFU g-1 dry soil). Consistent with previous data obtained with the reference fungus, migration with the migration-inciting fungi occurred only in the direction of the hyphal growth front. Remarkably, B. terrae BS001 provided protection from several antifungal agents to the canonical host L. sp. strain Karsten. Specifically, this host was protected from Pseudomonas fluorescens strain CHA0 metabolites, as well as from the anti-fungal agent cycloheximide. Similar protection by strain BS001was observed for T. asperellum, and, to a lower extent , F. oxysporum and R. solani. The protective effect may be related to the consistent occurrence of biofilm-like cell layers or agglomerates at the surfaces of the protected fungi. The current study represents the first r